Global studies : - Goodwin, Paul B. (McGraw-Hill, 2007)
From McGraw-Hill Contemporary Learning Series, the GLOBAL STUDIES volumes are designed to provide comprehensive background information and selected world press articles on the regions and countries of the world. This Thirteenth Edition of GLOBAL STUDIES: LATIN AMERICA includes introductory essays on Mexico, Central America, South America, and the Caribbean region, with concise reports and current statistics for each of the countries within these regions. This background information is complemented by a selection of articles from the world press.